SUMMER DIARRHEA IN THE SAN JOAQUIN VALLEY - Drake, Theodore (1950)
In laboratory, epidemiologic and clinical studies of 85 patients with diarrhea admitted to the General Hospital of Fresno County and the San Joaquin County Hospital during part of the summer of 1949 the following features were noted: 1. Cultures were positive for Shigella in about 45 per cent of the cases in the San Joaquin County Hospital and in about 15 per cent of those in the Fresno County Hospital. 2. In 80 per cent of cases in which there was gross blood in the stools before the third day of hospitalization, Shigella grew on cultures. No gross blood was noted in 27 per cent of cases in which Shigella was demonstrated. 3. The cases in which Shigella was demonstrated did not differ greatly from the others with regard to fever, leukocytosis, or response to therapy. 4. Salmonella organisms were not grown on cultures in any case. 5. Most of the patients were infants younger than one year of age. 6. Poor socio-economic and hygienic conditions characterized the households from which these county hospital patients came. 7. Household follow-up studies indicated that there had been one or more instances of diarrhea among household associates of approximately half the hospitalized patients at some time during the month prior to admission.